Dental caries and dental practice: a new approach from a collective health perspective - Luis Enrique Pérez Silva; Edgar Carlos Jarillo Soto (Social Medicine Publication Group, 2024)
Introduction: Traditional approaches to try to reduce dental caries have not been sufficient to support an effective dental practice in reducing and controlling the incidence of this disease, therefore, it is necessary to move towards a different, dialectical, comprehensive, multidimensional visión, with the privilege of studying processes of social determination for a greater and better capacity to know and understand this health problem. Objective: Rethink the reductionist logic on dental caries, with a new perspective from collective health, to understand the complex-structural determinations that affect this disease. Method: This essay proposes a new integrative look at dental caries as a determined, historical, social, economic, political, as well as biological process; expressed in a social space where inequalities in oral health are reproduced. Conclusions: To reduce the incidence of dental caries, it is necessary to rethink and question the practices of traditional dentistry and socially construct new collective, counterhegemonic knowledge, explaining its dynamics in a complex urban or rural territory, determined by the general system of relations and production social, a different alternative to functionalist health is collective health.